A functional proteomics approach links the ubiquitin-related modifier Urm1 to a tRNA modification pathway - Schlieker, Christian D. (National Academy of Sciences, 2008)
Urm1 is a highly conserved ubiquitin-related modifier of unknown function. A reduction of cellular Urm1 levels causes severe cytokinesis defects in HeLa cells, resulting in the accumulation of enlarged multinucleated cells. To understand the underlying mechanism, we applied a functional proteomics approach and discovered an enzymatic activity that links Urm1 to a tRNA modification pathway. Unlike ubiquitin (Ub) and many Ub-like modifiers, which are commonly conjugated to proteinaceous targets, Urm1 is activated by an unusual mechanism to yield a thiocarboxylate intermediate that serves as sulfur donor in tRNA thiolation reactions. This mechanism is reminiscent of that used by prokaryotic sulfur carriers and thus defines the evolutionary link between ancient Ub progenitors and the eukaryotic Ub/Ub-like modification systems.